2021
DOI: 10.3390/rs13122359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lunar Complex Illumination on In Situ Measurements Obtained Using Visible and Near-Infrared Imaging Spectrometer of Chang’E-4

Abstract: In-situ measurements of the spectral information on the lunar surface are of significance to study the geological evolution of the Moon. China’s Chang’E-4 (CE-4) Yutu-2 rover has conducted several in-situ spectral explorations on the Moon. The visible and near-infrared imaging spectrometer (VNIS) onboard the rover has acquired a series of in-situ spectra of the regolith at the landing site. In general, the mineralogical research of the lunar surface relies on the accuracy of the in-situ data. However, the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Some bright spots that were probably produced by stray light were also observed (Figure 1d). Shadows and stray light affect the spectral data to a certain extent (J. Xu et al., 2021). The areas with rocks, shadows, and bright spots were excluded when performing photometric model fitting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some bright spots that were probably produced by stray light were also observed (Figure 1d). Shadows and stray light affect the spectral data to a certain extent (J. Xu et al., 2021). The areas with rocks, shadows, and bright spots were excluded when performing photometric model fitting.…”
Section: Methodsmentioning
confidence: 99%
“…Shadows and stray light affect the spectral data to a certain extent (J. Xu et al, 2021). The areas with rocks, shadows, and bright spots were excluded when performing photometric model fitting.…”
Section: Writing -Original Draft: Jiafei Xu Meizhu Wangmentioning
confidence: 99%
“…That could be compatible with cyanobacterial life. Due to the fact, that materials such as regolith and basalts show an increased reflectivity in the red/IR region (Anbazhagan and Arivazhagan, 2009;Gaier et al, 2012;Xu et al, 2021), a FR enrichment analogous to Earth caves could be expected. Similar features (Sauro et al, 2020) and materials (Mandon et al, 2022) can be found on Mars, whose caves might also present a more hospitable environment than the surface (Léveillé and Datta, 2010;Irwin and Schulze-Makuch, 2020).…”
Section: Far-red Light Photosynthetic Adaptations In Cyanobacteriamentioning
confidence: 99%
“…An artifact absorption around 820 nm (Figure A2) is noticed in VNIS spectra and is probably caused by the F46 films in the multilayer insulation (Xu et al 2021) on the body and/or aluminum metal in the wheels of the Yutu-2 rover. This artifact is more obvious in VNIS spectra of darker pixels where the sunlight is shielded by local topography while the reflected and/or scattered sunlight with 820 nm absorption from the rover serves as a dominant light source.…”
Section: Correction Of Instrumental Artifactsmentioning
confidence: 99%